Peran Gender dalam Pemilihan Bahasa dan Gaya Bicara di Lingkungan Kerja - Trianjani, Mimin; Sofiana, Zulfa; S, Sugiarti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study discusses the role of gender in language and speaking style choices in the workplace, focusing on how gender differences affect communication patterns between individuals. In the workplace, communication is key to building relationships, conveying ideas, and resolving conflicts. However, gender differences can affect the way a person chooses words, intonation, and speaking style, which ultimately impacts communication effectiveness. This study uses a qualitative approach through observation and interviews in several work sectors. The results show that women tend to use a cooperative and supportive speaking style, while men are more dominant and direct in communication. These differences are influenced by cultural, social factors, and position in the organization. Understanding differences in communication styles based on gender is important in building an inclusive and productive work environment.